Nonlinear synchronization of fractional-order Lu and Qi chaotic systems - Yadava V.K.; Das S.; Cafagna D. (My University, 2025)
In this paper the synchronization between fractional order chaotic Lu and Qi systems is performed, based on Lyapunov stability theory and using a new lemma given for fractional order Caputo derivative. The new lemma is proficiently applied to design the nonlinear controller. The numerical results show that the method is easy to implement and reliable for the synchronization of two different fractional order chaotic systems. © 2016 IEEE.